1991
DOI: 10.1523/jneurosci.11-06-01855.1991
|View full text |Cite
|
Sign up to set email alerts
|

Learning-dependent neuronal activity in the premotor cortex: activity during the acquisition of conditional motor associations

Abstract: It has been proposed that the premotor cortex plays a role in the selection of motor programs based on environmental context. To test this hypothesis, we recorded the activity of single neurons as monkeys learned visuomotor associations. The hypothesis predicts that task-related premotor cortical activity before learning should differ from that afterward. We found that a substantial population of premotor cortex neurons, over half of those adequately tested, showed the predicted learning-dependent changes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
180
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(201 citation statements)
references
References 63 publications
(72 reference statements)
18
180
1
1
Order By: Relevance
“…6 shows population averages for IS-on period, but plotted over the entire learning period rather than divided into early, middle, and late phases of learning. In accord with previous results of PMd (Mitz et al, 1991;Brasted and Wise, 2004), the post-IS activity increased most dramatically at the time that the monkey's performance improved most rapidly, the middle phase of learning as defined here.…”
Section: Comparison Of Pmd and Putamen Population Activity Levelssupporting
confidence: 92%
See 1 more Smart Citation
“…6 shows population averages for IS-on period, but plotted over the entire learning period rather than divided into early, middle, and late phases of learning. In accord with previous results of PMd (Mitz et al, 1991;Brasted and Wise, 2004), the post-IS activity increased most dramatically at the time that the monkey's performance improved most rapidly, the middle phase of learning as defined here.…”
Section: Comparison Of Pmd and Putamen Population Activity Levelssupporting
confidence: 92%
“…Antecedents can include visual and other sensory inputs, and consequents usually involve movements or the targets of movement. Changes in task-related neuronal activity during arbitrary visuomotor learning have been described for dorsal premotor cortex (PMd) (Mitz et al, 1991;Brasted and Wise, 2004), supplementary eye field (Chen and Wise, 1995a, b), frontal eye field (Chen and Wise, 1995b), prefrontal cortex (Asaad et al, 1998;Pasupathy and Miller, 2005), hippocampus (Cahusac et al, 1993;Wirth et al, 2003), striatum Jog et al, 1999;Brasted and Wise, 2004;Pasupathy and Miller, 2005) and globus pallidus (Inase et al, 2001). Neuropsychological studies point to the same neural network (Petrides, 1985;Halsband and Passingham, 1985;Rupniak and Gaffan, 1987;Gaffan and Harrison, 1988;Canavan et al, 1989;Eacott and Gaffan, 1992;Murray and Wise, 1996;Ridley and Baker, 1997;Wang et al, 2000;Bussey et al, 2001Bussey et al, , 2002Brasted et al, 2002Brasted et al, , 2003Barefoot et al, 2002Barefoot et al, , 2003Nixon et al, 2004), as does the neuroimaging literature (Deiber et al, 1991(Deiber et al, , 1997Paus et al, 1993;Toni and Passingham, 1999;Toni et al, 2001Toni et al, , 2002Eliassen et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…A more ventral and rostral part of the between an imagined trigger stimulus and the motor vPMC is also suggested to be involved in the imagination commands. This interpretation is related to findings linking of complex movements [49], preparation of imitated the caudal part of the dPMC to the learning of visual movements [24], or imitation of movements in general conditional tasks both in monkeys and humans [17,33]. [41, 44,45].…”
Section: Introductionmentioning
confidence: 92%
“…The changes in neuronal activity during the whole learning process deserve study. Gradually, learning-related changes in neuronal activity have been shown in several brain areas, such as the PFC [58] , basal ganglia [59] , premotor cortex [60] and supplementary eye field [61] . Experiments in the PFC have shown that learning an arbitrary stimulus-response mapping causes the representation of movement direction to appear earlier in the delay period before the execution of an eye movement.…”
mentioning
confidence: 99%